Labor Union Membership and Minimum Wage in the Philippines - Mansueto, Ma. Kresna (Technium Social Sciences Journal, 2021)
This recent empirical study investigates the effect of labor union membership on minimum wage. After the diagnostic tests to select an appropriate estimation for this panel data, the study estimates the model using pooled-ordinary least square. The result indicates that across the Philippine regions, memberships to labor unions have positive, economically, and statistically significant consequences on the log value of the real minimum wage. It further claims that a one-percentage-point increase in the fraction of employed workers who are members of the labor union creates a 131% increase in the value of the real minimum wage. Other controlled variables that support recent studies are a higher level of education and productivity are positively related to minimum wages, while less than 40 hours work per week negatively associated with minimum wage.